SURFACE ALTERATION OF ARSENOPYRITE (FEASS) BY THIOBACILLUS FERROOXIDANS - Jones R.A.; Koval S.F.; Nesbitt H.W. (My University, 2003)
The surface of arsenopyrite was characterized after acidic, oxidative leaching in the presence of the bacterial species Thiobacillus ferrooxidans. Polished single-crystal grains of arsenopyrite were reacted for 1, 2, and 3 weeks with T. ferrooxidans suspended in a solution (pH 2.3) of essential salts (MgSO4.7H2O, [NH4]2SO4, KH2PO4, and KCl). Abiotic control experiments were conducted in identical solutions. Reaction between arsenopyrite and T. ferrooxidans in the essential salts solution produced a uniform solid FePO4 overlayer (~0.2 μm thick) on the arsenopyrite surface within 1 week. The overlayer was detected visually by scanning electron microscopy (SEM) and chemically by X-ray photoelectron spectroscopy (XPS). It could not be distinguished by energy-dispersive X-ray analyses. No overlayer formed in the abiotic control. The uniform thickness and lateral continuity of the overlayer suggest an inorganic origin promoted by bacterial production of Fe3+. Iron released from arsenopyrite was oxidized by bacteria and subsequently precipitated with PO43- (from the essential salts), forming ferric phosphate. After 2 and 3 weeks, SEM images revealed a roughened arsenopyrite surface, and XPS depth profiles indicated a progressively thicker phosphate overlayer and continued oxidation, diffusion, and dissolution of arsenopyrite beneath the overlayer. After only 1 week, the cells were isolated from the arsenopyrite surface by the uniform overlayer. Therefore, bacteria need not be attached to arsenopyrite to promote rapid reaction, and the mechanism of alteration at the arsenopyrite surface must have been inorganic. Because the delicate overlayer did not prevent continued alteration of arsenopyrite, FePO4 may not be an effective barrier to oxidation in the tailings environment. The FePO4 coating has likely formed in other experiments using these bacteria but was not detected because analytical techniques were not sufficiently surface sensitive to identify a separate, compositionally distinct overlayer. Some previous experimental results thus may be misleading or inapplicable to the tailings environment.
Keywords: arsenopyrite